2017
DOI: 10.1172/jci88881
|View full text |Cite
|
Sign up to set email alerts
|

Liver inflammation and fibrosis

Abstract: Chronic liver inflammation leads to fibrosis and cirrhosis, which is the 12th leading cause of death in the United States. Hepatocyte steatosis is a component of metabolic syndrome and insulin resistance. Hepatic steatosis may be benign or progress to hepatocyte injury and the initiation of inflammation, which activates immune cells. While Kupffer cells are the resident macrophage in the liver, inflammatory cells such as infiltrating macrophages, T lymphocytes, neutrophils, and DCs all contribute to liver infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
832
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 947 publications
(849 citation statements)
references
References 155 publications
10
832
0
7
Order By: Relevance
“…Consistent with above observation, we have found that Hsf1 303A/307A mice exhibit high levels of expression of specific Hsps (and likely other genes) in the liver, kidney, spleen and heart tissues and at least as we present in the liver tissue, this is associated with increased levels of CD11b and phosphorylated c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinases (ERK) signaling and an increased expression of transcription factors associated with lipogenesis. This phenotype is a hallmark of low, but sustained levels of inflammation that is observed following alterations in the liver metabolism induced by a variety of conditions that eventually can lead to fatty liver disease and hepatocellular carcinoma (47,48). Contrary to the mutant Hsf1 303A/307A mice that exhibit increased activity that leads to an age-dependent metabolic syndrome, the whole body deletion of hsf1 are resistant to multiple tumor types (3,7,49).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with above observation, we have found that Hsf1 303A/307A mice exhibit high levels of expression of specific Hsps (and likely other genes) in the liver, kidney, spleen and heart tissues and at least as we present in the liver tissue, this is associated with increased levels of CD11b and phosphorylated c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinases (ERK) signaling and an increased expression of transcription factors associated with lipogenesis. This phenotype is a hallmark of low, but sustained levels of inflammation that is observed following alterations in the liver metabolism induced by a variety of conditions that eventually can lead to fatty liver disease and hepatocellular carcinoma (47,48). Contrary to the mutant Hsf1 303A/307A mice that exhibit increased activity that leads to an age-dependent metabolic syndrome, the whole body deletion of hsf1 are resistant to multiple tumor types (3,7,49).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, obesity has been associated with the presence of other immune cells in liver, including T cells and neutrophils. Yukinori Koyama and David Brenner discuss the close connection between obesity, diabetes, hepatic inflammation, and the development of nonalcoholic fatty liver disease (NAFLD), which can progress to nonalcoholic steatohepatitis (NASH) and eventually frank cirrhosis due to sequential activation of inflammation and fibrosis (10).…”
Section: Mechanisms Of Inflammation-induced Insulin Resistancementioning
confidence: 99%
“…Liver damage causes inflammation, which accelerates fibrosis by releasing HSCstimulating cytokines [30][31][32]. Based on the severe hepatic injury with inflammation in the livers of the PbA-injected mice in this study, we evaluated whether PbA infection promotes liver fibrosis.…”
Section: Hepatic Fibrosis Is Enhanced In the Livers Of Pba-infected Micementioning
confidence: 99%